How Peace Takes Shape Locally: The Experience of Civil Resistance in Samaniego, Colombia. (April 2016) - Mouly, Cécile; Garrido, María Belén; Idler, Annette
Abstract : Drawing on the experience of Samaniego, Colombia, this article explores processes of civil resistance in the midst of armed conflict. Based on data from fieldwork in Samaniego and other localities in Colombia, as well as literature on civil resistance, peacebuilding, and rebel governance, we analyze the process of mobilization of the population of this war‐affected municipality against armed violence from its beginning in 1997 until the year 2014. As we contend, this process arose as the combined result of factors related to agency and structure. The national and departmental contexts, particularly the holding of peace negotiations between the government and National Liberation Army (ELN) rebels and the existence of similar local peace initiatives, contributed to the establishment of a propitious environment for the mobilization that took place in 1997 and led to the declaration of Samaniego as a peace territory. In terms of agency, two mayors and various civil society actors played a leading role in the process. Several factors accounted for the success of this initiative in achieving, at least to some extent, its objective of reducing violence. We cluster these into three sets of factors: structural factors, the characteristics of the civil resistance movement, and the strategic decisions made by the movement. A better understanding of these factors and their interactions can shed light on the dynamics of civil resistance in situations of armed conflict and their outcomes, offering significant insights into scholarly debates about civil resistance and local peace formation.